Identifying competencies for future graphic design graduates in Malaysia: A Delphi study - Wong, Shaw-Chiang; Zaffwan Idris, Muhammad; Tan, Wee-Chuen (Journal of Graphic Engineering and Design, 2021)
Traditionally, graphic design (GD) education focuses on the training of technical production skills to prepare graduates for entry-level employment. However, due to the new challenges and the expanding opportunities of emerging practices, GD graduates are expected to master a wide range of additional competencies beyond traditional scope. The study aims to identify the competencies required by future GD graduates in the context of Malaysia. A two-round modified Delphi technique was used to gain consensus from a panel of experts consisted of design educators and industry practitioners regarding the competencies needed by the graduates for effective work performance. A total of 108 competencies were generated. All accepted competencies were ranked ‘very important’ and ‘extremely important’ by at least 75 percent of the respondents in Round Two. These competencies could be classified into 29 subdomains under five components, i.e., cognitive competence, functional competence, personal competence, ethical competence, and meta-competencies. The findings of this study are useful for enhancing the education and employability of graphic designers as they provide a common vocabulary to relevant stakeholders about the standards of performance for new entrants to the GD profession. Article history: Received (March 22, 2021); Revised (May 21, 2021); Accepted (June 4, 2021); Published online (September 1, 2021)